A COMMOGNITIVE STANDPOINT: THE PROCESS OF PROBLEM-SOLVING IN POLYHEDRON - Azizah, Fita Nuril; Wulan, Eka Resti; Rahayu, Dwi Shinta (Universitas Tanjungpura, 2023)
Abstract This study aims to describe students